0005 Leading causes of child injury deaths in new york city. (26th April 2015) - Conderino, Sarah; Fung, Lawrence; Spira-Cohen, Ariel; Marcum, Jennifer; Norton, Jennifer M; Caffarelli, Anna; Stayton, Catherine
Abstract : Statement of purpose: The New York City (NYC) Child Fatality Review Advisory Team 2014 report characterises patterns of child injury deaths in NYC with a special focus on motor vehicle (MV)-related injuries. Methods/Approach: Deaths among children aged 1–12yrs from 2003–2012 were identified from the NYC Bureau of Vital Statistics death records using the International Classification of Disease (ICD-10) codes V01-Y34. Detailed information about MV-related deaths among children and youth aged 1–17yrs from 2009–2011 was abstracted from review of Office of Chief Medical Examiner files and the NYC Department of Transportation Traffic Fatality Database. We calculated descriptive statistics including counts, proportions, and age-specific rates. Distances between MV crash location and place of residence were measured in blocks using the shortest route street network. Results: There were 438 injury deaths from 2003–2012 among children aged 1–12. Unintentional injury death rates were highest among boys, non-Hispanic black children, and children from very high poverty neighbourhoods. Intentional injury death rates (primarily homicides) were highest among children aged 1–2, non-Hispanic black children, and children from high and very high poverty neighbourhoods. The leading cause of injury death was MV-related injuries, followed by fire-related, suffocation, and falls. Of the 110 MV-related deaths, 71% (n = 78) were pedestrians. There were 48 MV-related deaths from 2009–2011 among children and youth aged 1–17. 65% were pedestrians, 23% MV passengers, 6% MV drivers, and 6% bicyclists. 33% of the child/youth pedestrian deaths occurred between the hours of 3PM to 8PM and 48% were struck by cars. Nearly two-thirds (61%) of the pedestrians were crossing midblock or against the traffic light at an intersection. Over one third (35%) of these pedestrians were hit by a motor vehicle within 2 city blocks of home, and almost two-thirds (61%) were within 10 city blocks of home. Conclusions: MV-related injuries represent the leading cause of injury death among children aged 1–12, and within NYC the majority of these injury deaths are among pedestrians. Significance and contribution to the field: We recommend continued efforts, such as those enabled by NYC's Vision Zero initiative, to make walking, bicycling, driving, and riding in a motor-vehicle safer in NYC.